The impact of plateletcrit on the diagnosis and management of gestational diabetes mellitus (Annals of Medical Research, 2024)
Aim: Gestational diabetes mellitus (GDM) is a condition that can cause serious maternal and fetal complications. Platelets are one of the cells that play an important role in inflammation in our body. In this study, we aimed to investigate whether there is a relationship between platelet values obtained by a simple blood count and GDM.Materials and Methods: Two groups consisting of 60 individuals with GDM and 250 healthy populations were created. Demographic characteristics, the sugar loading test results performed between 24th-28th weeks and simple complete blood count results including platelets, plateletcrit (PCT), platelet distribution width (PDW), and mean platelet volume (MPV)) were analyzed with SPSS.Results: When comparing the ages, BMI, average blood pressure, heights, and gestational weeks of both groups, there was no any significant differences (p>0.05). In terms of the hemoglobin, platelet, and white blood cell counts, there wasn’t any significant differences between the two groups (p>0.05). MPV, PDW and PCT values ​​were significantly increased in patients with GDM compared to healthy pregnant women (p
Keywords: Blood count; Gestational diabetes mellitus; Plateletcrit; Mean platelet volume; Platelet